PENINGKATAN KEPUASAN DAN KUALITAS LAYANAN ELEKTRONIK (E-SERVQUAL) PELATIHAN DAN SERTIFIKASI DARING PT AMD ACADEMY - Mustaqim, Satrio Adhi Imam; Muslichah, Istyakara (Fakultas Teknologi Informasi dan Industri Unisbank, 2025)
The ease of internet access has changed the behavior of Indonesian society, driving the transformation from traditional marketing to digital marketing. To optimize digital marketing strategies, workforce training is essential to meet the demands of the industry. However, there are already competitors offering online training programs for professionals, necessitating an evaluation of services to enhance the offerings of PT AMD Academy. This program assesses satisfaction levels and the quality of electronic services provided by PT AMD Academy’s digital marketing training. A mixed-method approach was employed across three stages: interviews with the company (internal perspective), participant questionnaires, and follow-up interviews with questionnaire respondents (external perspective). Data was collected using E-SERVQUAL, encompassing variables such as website design, reliability, responsiveness, trust, personalization, overall service quality, and customer satisfaction. The findings of the program indicate that overall, participants were highly satisfied with the training services they received, with satisfaction driven by the adequate platform support, appealing and user-friendly website and LMS design, adherence to SKKNI standards, and the responsiveness of the instructors in guiding participants through a training process that was easy to follow for beginners. Additionally, the certification is aligned with professional requirements and current industry trends.